2012
DOI: 10.1007/s00795-011-0550-7
|View full text |Cite
|
Sign up to set email alerts
|

Irsogladine maleate ameliorates inflammation and fibrosis in mice with chronic colitis induced by dextran sulfate sodium

Abstract: Intestinal fibrosis is a common and severe complication of inflammatory bowel disease (IBD), especially Crohn's disease (CD). To investigate the therapeutic approach to intestinal fibrosis, we have developed a mouse model of intestinal fibrosis by administering dextran sulfate sodium (DSS) and examining the effects of irsogladine maleate (IM) [2,4-diamino-6-(2,5-dichlorophenyl)-s-triazine maleate], which has been widely used as an antiulcer drug for gastric mucosa in Japan, on DDS-induced chronic colitis. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The blockade of TGF-β signaling, either at the extracellular or intracellular level, is a strategy for preventing fibrosis [45]. ECM degradation is mediated by MMPs (a marker of fibrosis) and TIMPs [46]. MMPs and TIMPs are central to the ECM turnover and actively regulate inflammation and remodeling [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of TGF-β signaling, either at the extracellular or intracellular level, is a strategy for preventing fibrosis [45]. ECM degradation is mediated by MMPs (a marker of fibrosis) and TIMPs [46]. MMPs and TIMPs are central to the ECM turnover and actively regulate inflammation and remodeling [45].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the activity of MMPs was controlled by transcriptional regulation, proenzyme activation by TIMPs [47]. Yamaguchi reported that the mRNA expression levels of TGF-β1, MMP-2 and TIMP-1 were markedly increased in chronic dextran sulfate sodium-induced colitis in comparison to control mice [46]. Ding reported that homocysteine promoted intestinal fibrosis in a rat model of trinitrobenzene sulfonic acid (TNBS)-induced colitis and homocysteine increased the mRNA expression of TGF-β1, MMP-2, -9 and TIMP-1 in the colonic tissue of rats with TNBS/ethanol-induced colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1984, various mechanisms of action of IM to protect the mucosa in the gastrointestinal tract were reported, 14) including a few articles referring to anti-inflammatory effects in colitis. Among these reports, Yamaguchi et al showed that IM prevented fibrosis in a dioctyl sodium sulfosuccinate (DSS)-induced colitis model through suppressing the production of proinflammatory cytokines, 15) and Kamei et al reported that one of the mechanisms underlying amelioration of experimental colitis by IM may be correlated with secretion of mucus preventing bacterial invasion by disrupting mucosal integrity induced with indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Several recent reports have indicated that IM has antiinflammatory and protective effects in areas of the gastrointestinal mucosae other than the stomach. 15,16) The administration of IM by enema was shown to improve chronic experimental colitis induced by dextran sulfate sodium, suggesting that topical IM therapy could downregulate cytokine production.…”
mentioning
confidence: 99%
“…Animal models of fibrosis have been recently summarized and reviewed by Pizarro and colleagues [36,37]. In most of the animal models, fibrosis is either induced by chemicals such as dextran sodium sulfate [38,39,40] or 2,4,6- trinitrobenzenesulfonic acid [41,42,43,44,45,46,47,48], or by bacterial cell wall products such as peptidoglycan [49,50]. …”
Section: Why Is Fibrosis Research In Ibd Not More Advanced?mentioning
confidence: 99%